Mathematical and Statistical Modelling of Impact Symptoms and Application to Tomato - Herold, B.; Oberbarnscheidt, B.; Jakovác, F.; Kovács, L.; Borsa, B. (International Journal of Horticultural Science, 2002)
Drop tests were performed with different tomato cultivars. „Rupture" and „no rupture" conditions were determined as results. The proportion of „rupture" was shown versus the drop height and the relationships were described by a logistic function. The different cultivars are compared on this basis. The tests and results are suitable for the evaluation of stress sensitivity of tomatoes.